The Literature Review of Service Quality on Customer Satisfaction in Indonesian Banks - Daffa Quthbir Robani; Daffa Dwi Saputra; Yoga Aditiya Pratama; Mohamad Zein Saleh (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Service quality is a crucial element in determining the level of customer satisfaction in the banking sector. This study aims to analyze the relationship between service quality and customer satisfaction in Indonesian banks. The main focus lies on how banks are able to create quality services to maintain customer loyalty. This article uses the literature review method to identify factors that influence service quality, strategies implemented, and perceived benefits. The results show that service quality has a significant effect on the level of customer satisfaction. Service improvement strategies such as technology development, employee training, and effective communication are the keys to success.